Cortical representation of novel tool use: Understanding the neural basis of mechanical problem solving - Clara Seifert; Thabea Kampe; Cilia Jäger; Jennifer Randerath; Afra Wohlschläger; Joachim Hermsdörfer (NeuroImage)
Introduction: Using tools effectively is a fundamental human ability. Besides the proper recall of semantic knowledge, the application of mechanical problem solving strategies allows one to execute tool-related tasks properly. Past fMRI studies have shown a mainly left-lateralized network, including ventral, ventro-dorsal, and dorso-dorsal streams while using familiar tools with access to semantic information. However, to what degree the network is recruited when applying mechanical problem solving strategies to handle novel tools remains unclear. Methods: An event-related fMRI study including 22 participants was conducted. During scanning, participants had to manipulate novel tools, the function of which they could infer by mechanical problem solving. Brain activity was measured during actual novel tool use and selection, both during the planning and execution phase. Results: Similar brain activation during tool use and tool selection could be observed, ranging from left-hemispheric inferior parietal to frontal regions in the ventro-dorsal stream with lack of ventral activation. Task-specific activations were more pronounced during the planning phases. Discussion: During mechanical problem solving brain activation is more pronounced in the ventro-dorsal stream, where mechanical understanding and motor control need to be integrated. Similar networks recruited during tool selection compared to tool use trials reflect mental simulation strategies used to determine the appropriate tool-recipient fit. The ventral stream, linked to the recall of semantic knowledge, plays a subordinate role during this task and a stronger involvement of anterior regions reflect the relevance of the frontal lobe contributing to mechanical problem solving.